2018
DOI: 10.1016/j.cmet.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat, but Not Protein or Carbohydrate, Regulates Energy Intake and Causes Adiposity in Mice

Abstract: The impacts of different macronutrients on body weight regulation remain unresolved, with different studies suggesting increased dietary fat, increased carbohydrates (particularly sugars), or reduced protein may all stimulate overconsumption and drive obesity. We exposed C57BL/6 mice to 29 different diets varying from 8.3% to 80% fat, 10% to 80% carbohydrate, 5% to 30% protein, and 5% to 30% sucrose. Only increased dietary fat content was associated with elevated energy intake and adiposity. This response was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
185
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(223 citation statements)
references
References 59 publications
18
185
4
1
Order By: Relevance
“…29 At the same time, caloric intake was higher in the HFD versus the SD group (Figure 4) and this result 30 is in accordance with the literature (Hu et al, 2018a;Kleinert et al, 2018;Yang et al, 2014). The 31 high energy density found in the HFD (5.439 kcal/g) compared to the SD (3.080 kcal/g), particularly 32 from fat (58.2% vs 11.7%, respectively), support the caloric intake higher in the HFD group and it is 33 in accordance to a recent study where the authors suggested that the amount of fat from an HFD, but 34 not protein or carbohydrate, is the cause of adiposity increases in mice (Hu et al, 2018a). Further, we 35 also found an increase of adipose tissue in the HFD groups when compared to SD groups for 1 retroperitoneal (Figure 5 A) and epididymal adipose tissue (Figure 5 B).…”
Section: Differential Gene Expression In the Nucleus Accumbens -Transsupporting
confidence: 82%
“…29 At the same time, caloric intake was higher in the HFD versus the SD group (Figure 4) and this result 30 is in accordance with the literature (Hu et al, 2018a;Kleinert et al, 2018;Yang et al, 2014). The 31 high energy density found in the HFD (5.439 kcal/g) compared to the SD (3.080 kcal/g), particularly 32 from fat (58.2% vs 11.7%, respectively), support the caloric intake higher in the HFD group and it is 33 in accordance to a recent study where the authors suggested that the amount of fat from an HFD, but 34 not protein or carbohydrate, is the cause of adiposity increases in mice (Hu et al, 2018a). Further, we 35 also found an increase of adipose tissue in the HFD groups when compared to SD groups for 1 retroperitoneal (Figure 5 A) and epididymal adipose tissue (Figure 5 B).…”
Section: Differential Gene Expression In the Nucleus Accumbens -Transsupporting
confidence: 82%
“…High‐fat diet is a widely adopted method to induce obesity, non‐alcoholic fatty liver and T2DM, in which IR is widely considered the ‘common soil’ of those metabolic disorders . Maternal obesity is afflicted with many maternal obstetric complications in the offspring including high blood pressure, obesity, gestational diabetes and increased perinatal morbidity .…”
Section: Discussionmentioning
confidence: 99%
“…Our data confirmed that HFD led to IR and metabolic High-fat diet is a widely adopted method to induce obesity, non-alcoholic fatty liver and T2DM, in which IR is widely considered the 'common soil' of those metabolic disorders. [20][21][22] Maternal obesity is afflicted with many maternal obstetric complications in the offspring including high blood pressure, obesity, gestational diabetes and increased perinatal morbidity. 23 Several factors are involved in the progression of IR induced by HFD including inflammation, excessive ROS, abnormal immune response, lipotoxicity and altered glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported to cause acute pancreatitis and kidney failure in some patients (Hu et al, 2018). However, it has been reported to cause acute pancreatitis and kidney failure in some patients (Hu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most recent therapies for T2D, Byetta, targets GLP-1 receptors on β-cells to stimulate insulin secretion, and studies in mice suggest that it also increases β-cell mass. However, it has been reported to cause acute pancreatitis and kidney failure in some patients (Hu et al, 2018). Therefore, there is a need for the development of novel therapies with minimal side effects that can enhance pancreatic β-cell function and β-cell mass for glucose utilization.…”
Section: Introductionmentioning
confidence: 99%